Relationship Between Nurses’ Readiness and Institutional Readiness in Developing Nursing Career Paths in Public Health Centers - Tuti Afriani; Rr. Tutik Sri Hariyati; Dyah Fitri Wulandari (Fakultas Ilmu Keperawatan Universitas Indonesia, 2021)
Nursing career paths in public health centers have not been well established compared with nurses in hospitals. It is because the nursing career path has a different organizing system, which then becomes an obstacle in implementing the career path for nurses in primary health care. Therefore, this study aimed to identify the relationship between institutional and nurses’ readiness in implementing nursing career paths within public health centers. A cross-sectional study design with questionnaire as instrument was used in this research. A consecutive sampling technique was used to select 93 nurses from 13 public health centers. Furthermore, to identify the objective of this research, the Spearman’s correlation coefficient was used to determine the relationship between paired data. The results found that institutional readiness was 64 or 71.9% of maximum values, yet nurses’ readiness was 112 or 74.5% of maximum values. Thus, it can be concluded that there was a meaningful relationship between institutional and nurses’ readiness with career path implementation (p<0.001), indicating a strong positive relationship (r= 0.521). The results of this study are expected to become a baseline data for public health centers and public health offices to establish a professional nursing career path in public health centers. Abstrak Kesiapan Individu Berhubungan dengan Kesiapan Institusi dalam Penerapan Jenjang Karir Perawat di Puskesmas. Implementasi jenjang karir perawat di puskesmas belum terbentuk seperti pelaksanaan jenjang karir perawat di rumah sakit. Pengorganisasi jenjang karir yang berbeda pada pelayanan primer menjadi kendala dalam implementasi jenjang karir perawat di puskesmas. Tujuan dari penelitian ini adalah untuk mengidentifikasi hubungan kesiapan institusi dan kesiapan perawat dalam penerapan jenjang karir perawat di puskesmas. Desain penelitian menggunakan cross sectional menggunakan kuesioner kepada 93 perawat pada 13 puskesmas. Teknik pengambilan sampel adalah convenience sampling. Data dianalisis menggunakan uji korelasi Spearman yang melihat hubungan kesiapan perawat dengan kesiapan intitusi dalam pengembangan jenjang karir perawat di puskesmas. Hasil didapatkan rerata kesiapan insitusi 64 (71,9% dari nilai maksimal), sedangkan kesiapan perawat didapatkan hasil lebih tinggi yaitu 112 (74,5%). Terdapat hubungan secara bermakna kesiapan institusi dengan kesiapan perawat dalam penerapan jenjang karir di puskesmas dengan p< 0,001, arah hubungan positif, dan kekuatan hubungan cukup kuat yaitu r= 0,521. Penelitian ini menjadi data dasar agar puskesmas dan dinas kesehatan dapat menerapkan jenjang karir perawat profesional di puskesmas. Kata Kunci: implementasi, jenjang karir, kesiapan, perawat, puskesmas